Penerapan Flipbook pada Mata Pelajaran Dasar-Dasar Ketenagalistrikan untuk Meningkatkan Hasil Belajar Siswa - Hendri, Tania; Dewi, Citra (Jurnal Pendidikan Teknik Elektro, 2024)
This research aims to determine the impact of the application of flipbook learning media on the learning outcomes of TITL students in class X SMK Negeri 2 Payakumbuh. To improve student learning outcomes, a more interesting and interactive learning media is needed. This study uses a type of experimental research in the form of a quasi-experiment with a pretest-posttest non-equivalent control group design. This study used research instruments pre-test and post-test questions in objective form to see the learning outcomes of students and tested using a validity test, reliability test, differentiation test, and question difficulty index to determine the feasibility of the instruments used. The results showed an increase in student understanding supported by the results of the Independent Samples Test, and the completeness of student learning outcomes using flipbook media was better than conventional learning. Student learning outcomes after applying flipbook media are improved, so flipbook media has a positive impact in improving student learning outcomes. However, it should be noted that this study has some limitations, such as limited coverage to one school and one subject. A follow-up study involving more schools and subjects could provide greater insight into the application of this media. In addition, the factors of students' motivation and previous experience in the same subject may also be important considerations in future research. This research provides a strong foundation for curriculum development and learning approaches to improve students' understanding of electricity fundamentals.